2016
DOI: 10.1016/j.chb.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Do learners’ characteristics matter? An exploration of mobile-learning adoption in self-directed learning

Abstract: a b s t r a c tThis paper aims to identify individual characteristics that motivate learners to use mobile-learning. It sheds light on our current knowledge by a) examining an m-learning adoption model which accounts for learners' characteristics (learning style and personal innovativeness) in addition to previously studied mobile platform characteristics and b) considering the context in which learning occurs (formal and informal). A framework has been introduced and empirically tested. Results suggest that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
1
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 65 publications
7
83
1
6
Order By: Relevance
“…This study is a study to find out the usefulness of wiki technology which is supported by a seamless learning approach in learning Chinese. The finding of the study show that the new ICT form of technology wiki supported by seamless learning can effectively help students synergize formal and informal learning as well as language learning spaces both individually and socially (Karimi, 2016;Wong & Looi, 2011;Wong et al, 2015).…”
Section: E20)"mentioning
confidence: 91%
“…This study is a study to find out the usefulness of wiki technology which is supported by a seamless learning approach in learning Chinese. The finding of the study show that the new ICT form of technology wiki supported by seamless learning can effectively help students synergize formal and informal learning as well as language learning spaces both individually and socially (Karimi, 2016;Wong & Looi, 2011;Wong et al, 2015).…”
Section: E20)"mentioning
confidence: 91%
“…In academics, despite a large number of prior studies devoted to understanding mobile learning adoption and usage, most of these studies identified its antecedents from a technical‐centered perspective (Wang et al , ). Factors such as perceived usefulness, effort expectancy and performance expectancy are identified to influence initial adoption of mobile learning (Karimi, ). However, the underlying process of students' learning motivation forming and its impacts on mobile learning behaviors have seldom been explored, especially in the post‐adoption stage(eg, Kim, Lee, & Rha, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many learners' characteristics play a role in their level of SDLR. For instance, Karimi (2016) proposed that learner characteristics such as age, gender, and previous experience may act as either a facilitator or barrier to SDL. McCollin (2000) in the USA reported that gender was a factor affecting student-centered behavior.…”
Section: Discussionmentioning
confidence: 99%